2007
DOI: 10.1016/j.rapm.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guidance With Nerve Stimulation Reduces the Time Necessary for Resident Peripheral Nerve Blockade

Abstract: During resident teaching, ultrasound-aided peripheral nerve-stimulated block required less time to perform than did nerve-stimulator-guided blocks. Fewer needle insertions were required to perform the ultrasound-guided blocks, and there were fewer blood vessel punctures when ultrasound was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 21 publications
0
32
1
3
Order By: Relevance
“…Orebaugh et al reported recently that the time to perform the blocks varies between 1.8 minutes (ultrasound-guided techniques) and 6.5 minutes (neurostimulation) [15]. These times were shorter than those reported in our study and most likely have less influence on on-time transfer to the OR.…”
Section: Discussioncontrasting
confidence: 58%
“…Orebaugh et al reported recently that the time to perform the blocks varies between 1.8 minutes (ultrasound-guided techniques) and 6.5 minutes (neurostimulation) [15]. These times were shorter than those reported in our study and most likely have less influence on on-time transfer to the OR.…”
Section: Discussioncontrasting
confidence: 58%
“…1,2,8,9,[11][12][13][14][17][18][19]21,25,27,28,30,[35][36][37][41][42][43]45 The lists include phrenic nerve block, recurrent laryngeal nerve block, brachial plexus palsy/neuritis, Horner's syndrome, bronchospasm, spinal blockade, and cardiac arrest. The most common side effect noted in prior reports is ipsilateral phrenic nerve block, which may occur in up to 100% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,34,44 Reported complications of interscalene anesthesia include: seizure, cardiovascular collapse, pneumothorax, intraneural injection, spinal cord injection, brachial plexitis, auditory disturbance, dyspnea secondary to phrenic nerve palsy, chronic Horner's syndrome, pseudo aneurysm, and permanent paresthesias. 1,2,8,9,[11][12][13][14][17][18][19]21,[26][27][28]30,[35][36][37][41][42][43]45 In some anecdotal case reports, authors have expressed a concern that there would likely be an increased risk of serious complications if the procedure were to be performed after induction of general anesthesia. 3,34 However, we are not aware of any study which actually documents increased complications associated with interscalene anesthesia performed after induction of general anesthesia or compares complications in nonanesthetized patients versus those under general anesthesia.…”
mentioning
confidence: 99%
“…Despite the growing popularity of ultrasound-guided regional anesthesia techniques, many centers still commonly use electrical stimulation for teaching purposes [8] or because of the high cost of ultrasound machines. However, Chan et al [9] reported that ultrasound guidance improved the success rate of axillary brachial plexus block, with or without electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%